Unexpected Jeopardy: CMR Assist in Diagnosis of Atypical Chest Pain Patient Which Turns Out to be Chronic Aortic Dissection and Cardiac Schwannoma - Chotenimitkhun, Runyawan (The Bangkok Medical Journal, 2023)
A 60-year-old obese woman who had intermediate probability of coronary artery disease presented with atypical chest pain. The obstructive coronary artery disease was suspected. There were non-diagnostic results from basic cardiac investigation and echocardiogram. She was referred to stress cardiovascular magnetic resonance (CMR). CMR is a safe comprehensive imaging modality includes left ventricular function, stress perfusion study and late gadolinium enhancement to identify myocardial ischemia and myocardial infarction. Moreover, the CMR study can provide information of great vessels e.g. aorta and its complication as in this case. The right-sided structures were easily evaluated without body habitus limitation. She was diagnosed chronic aortic dissection and right atrial malignant cardiac tumor which pathologically confirmed cardiac schwannoma. Finally, she got accurately diagnosis which guided prompt surgical management and saved her live.